Potensi Budidaya Laut dengan Menggunakan Konsep Integrated Multi-Trophic Aquaculture (IMTA) - Rahmadani, Thoy Batun Citra; Muahiddah, Nuri (LPPM Universitas Mataram, 2024)
Aquaculture is an activity that produces waste in its production. Waste in the aquatic environment is dangerous because it can cause pollution. Source of aquaculture waste come from unetaen feed, feces and excretion products. Preventing this waste can be done by implementing an environmentally friendly aquaculture sistem that is in accordance with blue economy principles in order that aquaculture can be sustainable. One sistem that can be used is implementing Integrated Multi-Trophic Aquaculture (IMTA). IMTA is a aquaculture activity that apllies an integartion sistem between several species that are reared together. The IMTA principle is the use of nutrients in one rearing with the result that does not competition between spescies. The advantages of IMTA can minimize waste and increase profits because it can harvest more than one species.